Legal Sanctions in Environmental Crimes: Between Effectiveness and Obstacles - Bahutala, Andris E.; Aswar, Asrul (Estudiante Law Journal, 2025)
The purpose of this paper is to evaluate the effectiveness of the application of criminal sanctions based on Law No. 32 of 2009 concerning Environmental Protection and Management and to identify the obstacles to its implementation in the context of environmental law enforcement in Indonesia. The writing method uses a juridical-normative approach to the study of laws and regulations and a qualitative approach through case studies of environmental court decisions and interviews with law enforcement officers. The analysis and discussion focus on the form of criminal sanctions (imprisonment and fines), the principle of ultimum remedium, the still limited deterrent effect, as well as technical obstacles to proof, coordination between agencies, and low public awareness and participation. Based on these findings, the conclusion states that although the legal framework for environmental criminal sanctions is comprehensive, its effectiveness is still hampered by institutional and procedural aspects; therefore, recommendations are directed at strengthening the technical capacity of officers, harmonizing regulations, and increasing collaboration between agencies and public education so that criminal sanctions can function optimally as an instrument for preventing and eradicating environmental crimes.